2003
DOI: 10.1001/archsurg.138.7.707
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Roux-en-Y Gastric Bypass in the "Megaobese"

Abstract: Hypothesis: Laparoscopic Roux-en-Y gastric bypass is a safe and effective procedure in patients with a body mass index (BMI; calculated as weight in kilograms divided by the square of height in meters) of 70 or greater. Design: A retrospective analysis of patients with a BMI of 70 or greater who underwent laparoscopic Rouxen-Y gastric bypass by a single surgeon. Setting: A university-affiliated community hospital in Allentown, Pa. Patients: A nonconsecutive series of 9 patients with a BMI of 70 or greater who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 6 publications
0
9
0
4
Order By: Relevance
“…Numerous technical modifications have been proposed relating to gastric pouch construction, gastro-jejunal anastomosis, and length of alimentary and biliopancreatic limbs. RYGB usually results in 60% to 70% EWL [75,101,138,173,222,273], but the procedure is much better accepted in the United States (about 70% of all procedures) as compared to Europe [332].…”
Section: Choice Of Proceduresmentioning
confidence: 99%
“…Numerous technical modifications have been proposed relating to gastric pouch construction, gastro-jejunal anastomosis, and length of alimentary and biliopancreatic limbs. RYGB usually results in 60% to 70% EWL [75,101,138,173,222,273], but the procedure is much better accepted in the United States (about 70% of all procedures) as compared to Europe [332].…”
Section: Choice Of Proceduresmentioning
confidence: 99%
“…5 Several studies have shown that bariatric surgery can be accomplished safely in super obese patients. 54,55 However, higher BMI should still be an important consideration in patient selection, as it correlates with a higher prevalence of comorbidities, longer operative times, and higher rates of conversion to open procedures. 56 In conclusion, presence of diabetes, open surgery, and early surgeon experience are associated with increased risk of complications after GBP.…”
Section: Commentmentioning
confidence: 99%
“…Further subdivision of obesity into different groups according to BMI has become necessary for risk stratification purposes and long-term survival estimates. Patients with BMI>70 kg/m 2 present a challenging subgroup of the obese population because of limitations on diagnostic work-up and higher prevalence of perioperative complications [7,8]. The presence of severe accompanying comorbidities such as hypoventilation syndrome, sleep apnea, severe hypertension, insulin-dependent diabetes mellitus type II, deep vein thrombosis, and severe venous stasis disease, puts these patients at significantly higher risk for increased postoperative morbidity and mortality [4].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been published regarding the optimal perioperative management of these patients [6][7][8], while the most advantageous surgical approach still remains controversial. The major hazard when operating on these patients is the lack of sufficient pulmonary and cardiovascular reserve necessary to survive the difficulty of the operation and, in particular, any complication that may occur.…”
Section: Introductionmentioning
confidence: 99%